Modeling and Analysis of Information Security in Supply Chain Management - Al-Nunu, Ahmed Maher (2006)
A Master of Science thesis in Engineering Systems Management Submitted by Ahmed Maher Al-Nunu Entitled, "Modeling and Analysis of Information Security in Supply Chain Management," June 2006. Available are Both Soft and Hard Copies of the Thesis.